2015
DOI: 10.6061/clinics/2015(02)13
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors and T lymphocyte counts in Brazilian peacekeepers

Abstract: OBJECTIVE:To investigate the associations between psychosocial factors and peripheral blood CD4 and CD8 T lymphocyte numbers in Brazilian peacekeepers.METHODS:Venous blood was collected from 759 peacekeepers who had just returned from a peace mission in Haiti. Among the 759 soldiers, 642 individuals completed the psychosocial measures. CD4 and CD8 T lymphocyte counts were measured by flow cytometry using a commercially available kit. Psychosocial factors, including military peace force stressors, clinical stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…One study mentioned that when peacekeepers’ hardiness were high, their psychological distress became low [ 128 ]. One study found no association between psychosocial factors (military peace force stressors, clinical stress, anxiety and depression) and blood T lymphocyte among Brazilian peacekeepers in Haiti [ 129 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study mentioned that when peacekeepers’ hardiness were high, their psychological distress became low [ 128 ]. One study found no association between psychosocial factors (military peace force stressors, clinical stress, anxiety and depression) and blood T lymphocyte among Brazilian peacekeepers in Haiti [ 129 ].…”
Section: Resultsmentioning
confidence: 99%
“…A number of troop-contributing countries such as Australia and Netherland also explored psychological factors as health risk factors of UN peacekeepers in host countries such as Lebanon and Haiti. Due to missing hometown, disharmony in interpersonal relationships, and personal barriers to disclose experiences could lead to peacekeepers’ psychological distress such as anxiety and depression during and after deployment [ 49 , 104 , 124 , 129 ]. Natural environmental factors and behavioral lifestyle factors were also seemed to be important health risk factors of UN peacekeepers multiple troop-contributing such as Finland and China, and host countries such as the Democratic Republic of Congo and Somalia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation